Syringolaimus magdae Coelho Lima, Lins, Da Silva & Esteves 2009 - Tchesunov, Alexei V. (Zenodo, 2017)
Syringolaimus magdae Lima, Lins, Da Silva & Esteves, 2009. Lima et al ., 2009: p. 125-127, figs 3–4 (South–West Atlantic, off coast of Brazil, Campos Basin, 1050 m, siltclay), one male. Cuticle smooth along the entire body or striations not easily observed. Ventral pore situated at 35.2% of pharynx length from anterior end; ventral gland cell body present. Caudal glands and spinneret present. Monorchic. No supplementary organs mentioned. Syringolaimus marisalbi Platonova & Mokievsky, 1994 sp. inq. Platonova & Mokievsky, 1994: p. 9–10, figs 9–14 (White Sea, upper intertidal zone, fine sand with clay), males, females and juveniles. Body cuticle largely smooth but striated on tail. Spinneret present. Ovaries are described as straight (erroneously?). Amphids, ventral pore and ventral gland, male gonads, supplementary organs and caudal glands not mentioned. Apparently, close or may be identical to S. striatocaudatus . Syringolaimus nitidus Bussau, 1993 nom. nud. Bussau, 1993: p. 501–505, Abb. 216, 217. (South–East Pacific / Peru Basin/, 4100–4200 m, dark brown ooze with manganese nodules), males and females. Body cuticle with extremely fine annulations. Metanemes not observed. Ventral pore at a distance of 60 µm from anterior end (in a male), a bit anterior to the nerve ring. Spinneret evident but no caudal glands found. Monorchic. No supplementary organs mentioned. Published as part of Tchesunov, Alexei V., 2017, Free-living nematodes of the genus Syringolaimus de Man, 1888 (Nematoda, Enoplida, Ironidae) from the Angola Basin, South-East Atlantic Abyss, pp. 478-500 in Zootaxa 4306 (4) on pages 481-482, DOI:10.11646/zootaxa.4306.4.2, http://zenodo.org/record/845097